Understanding Tangent Plane and Normal Line using 3D Visualization - Dhakal, Bed Prasad (Mathematics Education Forum Chitwan, 2025)
This designed based, Technological Pedagogical Content Knowledge grounded qualitative research work explores how 3D visualizations support students' conceptual understanding in mathematics. Involving a sample of 13 university students during 2024 cohort while learning a course “Differential Geometry”, this study used observation checklist and classroom interactions notes as research tools. After analysis of collected data, the results showed that dynamic visualizations played a significant role in “formalized cognitive schema” as mental image, “improved conceptual understanding”, and “directed students’ attention and motivation toward dynamic media” effectively. So, this study established a connection between students’ learning outcomes and their learning engagement through dynamic 3D visual simulations while learning tangent plane and normal.